Lipopolysaccharides elicit an oxidative burst as a component of the innate immune system in the seagrass Thalassia testudinum - Loucks, Kyle (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.